Electronically-based governance system for public services: implementation in the Special Region of Yogyakarta, Indonesia - Rachmawati, Rini; Anjani, Dayang Fitri; Rohmah, Amandita 'Ainur; Nurwidiani, Tika; Almasari, Hidayah (Universitatea din Bucuresti, 2022)
The Electronically-Based Governance System (Sistem Pemerintahan Berbasis Elektronik/SPBE) deals with public services for the internal regional government and the public. This research aims to identify public services and their implementation, analyse the success and constraints in implementing public services, and elaborate recommendations. Secondary data were obtained through the local government website. Primary data were obtained through questionnaires filled out by staff in charge of technical SPBE at the Communications and Information Office in the Special Region of Yogyakarta and cities and districts in the region. Meanwhile, in-depth interviews were conducted with the head of the agency as a policy-making official related to SPBE. The result shows that the regional government has provided public services in both SPBE and innovative regional services. The users have felt the benefits of the public services provided. However, there are constraints related to users' ability in digital literacy and the availability of networks. In the future, both will become a priority to overcome.